The Legal Aspects of Hotel Tax Collection Using an Online System - Anbiya Resti Cendani; I Wayan Putu Sucana Aryana; Cokorde Istri Dian Laksmi Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The online hotel tax collection in Badung Regency is an implementation of an integrated, transparent, and efficient taxation system, in accordance with Government Regulation No. 82 of 2012 concerning the Implementation of Electronic Systems and Transactions. This system facilitates taxpayers in fulfilling their tax obligations by connecting various subsystems electronically and in real-time. This study aims to analyze the implications of the online hotel tax collection in Badung Regency and the challenges faced during its implementation. The research method used is normative legal research supported by empirical research, which involves direct field observation and comparison with relevant laws and regulations. The results show that online tax collection in Badung Regency has the potential to improve efficiency, transparency, and regional revenue, as well as provide convenience for taxpayers in reporting and payment. However, challenges such as digital literacy and data security remain barriers that need to be addressed. The commitment of the local government and public support are essential to overcoming these issues. With the continuous development of technological infrastructure and strict supervision, the online tax collection system can become an effective tool in driving economic growth and public welfare in Badung Regency.